Relevance and Limitations of Conventional Development Theory in the Context of Muslim-Majority Countries - Citra Hadi Habibie; Fauzan Fauzan; M.F Hidayatullah (ISTIFADA : Jurnal Ekonomi dan Lembaga Keuangan Syariah, 2026)
Modernization has become a dominant paradigm in contemporary development discourse, originating from Western intellectual traditions based on rationalism, secularism, industrialization, and economic expansion. Along with modernization, conventional development theories such as dependency theory and neoclassical growth theory emerged as frameworks for explaining economic transformation and development processes. However, their application in Muslim-majority countries raises questions regarding philosophical compatibility and practical limitations. This study aims to examine the relevance and limitations of conventional development theory from the perspective of Muslim-majority societies. This research uses a qualitative approach with library research methods based on books, journal articles, and conceptual literature. Data were analyzed descriptively to explore the philosophical and socio-economic foundations of conventional development theories. The findings show that modernization developed from the Renaissance and Enlightenment periods and was strongly influenced by secular values that prioritize rational and empirical approaches. Dependency theory highlights structural inequality in the global economy, while neoclassical growth emphasizes capital, labor, and technology as drivers of growth .From an Islamic perspective, development should integrate revelation, reason, and empirical knowledge to achieve justice, maslahah, and holistic welfare..